Analgesic and Antipyretic Activity of Sweet Orange Peel Methanol Extract - Silalahi, Elsa Debora; Lister, I Nyoman Ehrich; Fachrial, Edy (Biology, Medicine, & Natural Product Chemistry, 2023)
An analgesic-antipyretic drug widely used is paracetamol, which has various health benefits and several adverse effects. Therefore, various natural products have been extensively studied as alternative analgesic-antipyretics, one of which is sweet orange peel. This study aimed to investigate sweet orange peel's analgesic and antipyretic activity by in vivo methods. This experimental study evaluated the analgesic and antipyretic effects of sweet orange peel extract extracted by the maceration method. The analgesic effect was evaluated by tail immersion (Maximum Possible Analgesia) and acetic acid-induced writhing method (total abdominal writhing). Meanwhile, the antipyretic effect was evaluated by the brewer yeast-induced hyperpyrexia (body temperature) method. This study showed that sweet orange peel methanol extract significantly increased the maximum possible analgesia value (132.79%) and reduced the number of abdominal writhing (44.05%) at the highest dose of 750 mg/kg BW. It indicated analgesic activity from sweet orange peels. Meanwhile, the antipyretic effect of sweet orange peel methanol extract was observed from 1-4 hours after administration, and the highest percentage inhibition of body temperature 4 hours after administration was found in a moderate dose, that was 5.98% (P value: 0.042). Therefore, it can be concluded that sweet orange peel methanol extract has analgesic and antipyretic effects with an optimal dose range of 500-750 mg/kg BW.